Measuring customer satisfaction towards entertainment magazines of Utusan Karya Sendirian Berhad - Khalid, Mohamad Kamil Ariff; Wan Abdul Rahman, Wan Zuhaila; Muhammad, Norrini; Ismail, Normala; Abdul Rahim, Rozlan; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Entertainment magazines are magazines that provide readers with consistently updated entertainment news locally and internationally. This research aimed to identify the factors that influenced customers’ satisfaction. The target population of this research was students of quasi-government polytechnic, Kolej Politeknik MARA in Bangi, Malaysia. A total of 317 questionnaires were distributed. Using SPSS, it was found that the front page was the most influencing factor that affected customer satisfaction. However, it was also found that respondents were neither satisfied nor dissatisfied with entertainment magazines. It is suggested that continuous efforts and new marketing plans need to be carried out in order to improve customer satisfaction of the entertainment magazines. Post-purchase product satisfaction need to be studied as a continuation of this study.